Examination of Electrocardiography and 24-Hour Holter Electrocardiography Data of Children Presenting With the Complaint of Palpitation. - Mehmet Türe (Van Tip Dergisi, 2021)
INTRODUCTION: Introduction: Palpitations are the most common and most important symptoms of patients with rhythm disturbances. Rhythm disturbances may not be detected by electrocardiography.